Identification of Serum Exosomal hsa-circ-0004771 as a Novel Diagnostic Biomarker of Colorectal Cancer - Pan, Bei; Qin, Jian; Liu, Xiangxiang; He, Bangshun; Wang, Xuhong; Pan, Yuqin; Sun, Huiling; Xu, Tao; Xu, Mu; Chen, Xiaoxiang; Xu, Xueni; Zeng, Kaixuan; et al. (Frontiers in Genetics, 2019)
Background: Exosomal circular RNAs (circRNAs) in peripheral blood are considered as emerging diagnostic biomarkers of cancers. Owing to the lack of sensitive and specific biomarkers, a large number of colorectal cancer (CRC) patients were diagnosed in advanced stages leading to high mortality. This study aimed to identify circulating exosomal circRNAs as novel diagnostic biomarkers of CRC. Materials and Methods: Candidate circRNA was selected by integrating analysis of Gene Expression Omnibus (GEO) database with online program GEO2R. A total of 170 patients and 45 healthy controls were enrolled to assess the diagnostic value of circRNAs for CRC. Exosomes isolated from the serum of participants and cell cultured media were confirmed by transmission electron microscope (TEM), Nanoparticle Tracking Analysis and western blot. The expression and the diagnostic utility of circRNA were tested by qRT-PCR and receiver operating characteristic (ROC) analysis, respectively. Results: The circulating exosomal hsa-circ-0004771 with most abundant among the top ten differentially expressed circRNAs (fold change ≥1.5) was selected for further study based on the results of GEO dataset analysis. The up-regulated exosomal hsa-circ-0004771 was verified in serum of CRC patients compared to healthy controls (HCs) and patients with benign intestinal diseases (BIDs) by qRT-PCR. The area under the ROC curves (AUCs) of circulating exosomal hsa-circ-0004771 were 0.59 (95%CI, 0.457–0.725), 0.86 (95%CI, 0.785–0.933) and 0.88 (95%CI, 0.815–0.940) to differentiate BIDs, stage I/II CRC patients and CRC patients from HCs, respectively. The AUC was 0.816 (95%CI, 0.728–0.9) to differentiate stage I/II CRC patients from patients with BIDs. In addition, the elevated expression of exosomal hsa-circ-0004771 in the serum of CRC patients was tumor-derived. It was found that the expression of exosomal hsa-circ-0004771 was down-regulated expression of in the serum of postoperative CRC patients as well as cultured media of CRC cells treated with GW4869. Conclusions: Circulating exosomal hsa-circ-0004771 was significantly up-regulated in CRC patients and served as a novel potential diagnostic biomarker of CRC.